Sleeping Beauties in Anatomy Literature - Shiva Malgard; Mohsen Fazeli-Varzaneh; Gholamreza Hassanzadeh; Shadi Asadzandi (International Journal of Information Science and Management)
The study aimed to identify the most critical sleeping beauty papers in anatomy and calculate their awake intensity and year. The data score was defined with a Scopus query using advanced search. Since at least 10 years of sleep is necessary for a paper to be regarded, only papers published between 1970-2010 were included. The bibliographic and Citation Report features were exported in the CSV format. The B-score of the remaining documents was then calculated. The top 10 sleeping beauty documents had an awake year after 2010 in Anatomy. Based on the B-Score of the top 10 papers, the number of studies that cite sleeping beauties is increasing. Identifying the citation patterns of sleeping beauties can help analyze researchers' scientific behavior, examine the evolution of a particular discipline, and understand the delay in recognizing innovative processes.